Application (Gym Fit) As a Fitness Center Marketing Tool in Digital Era - Ahmad Ridwan; Ria Lumintuarso; Jodi Visnu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to produce an application that functions as a marketing tool for fitness centers in the digital era. This study uses the research and development (R&D) method, which consists of (1) collecting research results and information or often referred to as a preliminary study, (2) planning or planning, (3) developing an initial product or developing a preliminary form of product, ( 4) initial test or preliminary field testing, (5) revision of the first product preparation or main product revision, (6) main field testing of main field testing, (7) revision of operational product preparation or operational product revision, (8) trial operational product or operational field testing, (9) final product revision or final product revision. This application is called Gym Fit which consists of 4 main menus, namely education, profile of fitness center, personal trainer, and contact person. The results of the large-scale trial assessment of the developed product stated a total score of 70 with a percentage (4.8%) of the sample stating ENOUGH, then a total score of 452 with a percentage (31.4%) of the sample saying GOOD, and a total score of 918 with a percentage (63.75%) of the sample stating very good.